Comparison of the effect of chamomile, Ginger and vitamin B6 on treatment of nausea and vomiting in pregnancy: a randomized clinical trial - Hamideh Pakniat; Mohammad Reza Memarzadeh; Nezal Azh; Maryam Mafi; Fatemeh Ranjkesh (Mashhad University of Medical Sciences, 2018)
Introduction: Nausea and vomiting is of the common complain during pregnancy. Herbal medicine is among the traditional treatments. This study was performed with aim to compare the effects of chamomile, Ginger and vitamin B6 on treatment of nausea and vomiting in pregnancy.  Methods: This randomized clinical trial was performed on 105 pregnant women with gestational nausea and vomiting in Qazvin Health Centers in 2016-2017. The subjects were randomly assigned to three groups (intervention 1,2,3) (n=35 in each group). The intervention groups received oral capsule of chamomile, ginger and vitamin B6 for four days, three times a day. Rhodes index was used to assess nausea and vomiting before and 1 week after intervention. Data were analyzed by SPSS software (version 23) and t-test, Chi-square, Kruskal-Wallis and Wilcoxon. P<0.05 was considered statistically significant. Results: Before the intervention, no significant difference was observed between three groups in the mean of nausea, vomiting based on Rhodes index (p>0.05). Whereas, after the intervention, it showed significant decrease in three groups (P=0.001), but there was no significant difference between three groups in terms of decreased mean of nausea and vomiting (p>0.05). Conclusion: Chamomile, ginger and vitamin B6 are equally effective for decreasing nausea and vomiting in pregnancy and there is no significant superiority in therapeutic effects in any of the three drugs.